Biochemical and biological activities of recombinant S1 subunit of pertussis toxin. - Barbieri, J T (1990)
degP-deficient strains of Escherichia coli grown in M-9 medium supplemented with ZnCl2 expressed the recombinant S1 subunit of pertussis toxin (rS1) in a form electrophoretically identical to the authentic S1 subunit. Subcellular fractionation showed that the full-length form of rS1 was membrane associated, while proteolytic fragments of rS1 were present in the periplasm. rS1 was extracted from outer membrane preparations with 8 M urea and purified by gel filtration chromatography. Purified rS1 ADP-ribosylated transducin at a similar molar efficiency relative to authentic pertussis toxin and, when associated with the native B oligomer of pertussis toxin, elicited Chinese hamster ovary cell clustering.